From Bench to Bedside: Understanding Multiple Dimensions of Pediatric HIV in Kenya - Beima-Sofie, Kristin M. (My University, 2013)
Introduction: Globally, over 3.3 million children are infected with HIV. Despite significant progress, there is a need to better understand mechanisms for transmission and progression of HIV in children. In addition, among children receiving HIV care, it is important to determine the best ways to inform them about their diagnosis. Methods: Consistent with the University of Washington Public Health Genetics PhD requirement of including both genetic epidemiology and social/cultural domains, this PhD dissertation addresses two projects of relevance to children with HIV. The aim of the first project is to determine the role of selected genetic mechanisms influencing pediatric HIV acquisition and progression. The aim of the second project is to determine how, when and what healthcare providers decide to tell HIV-infected children about their diagnosis. For project 1, we used genetic epidemiology methods to evaluate the role of variations in innate immune system genes on infant HIV acquisition and progression in a Kenyan mother-to-child transmission (MTCT) cohort. Specifically, we genotyped infants from this cohort for 6 candidate and 118 haplotype-tagging polymorphisms in TLRs 2, 3, 4, 7, 8, and 9, MyD88 and TIRAP, and 144 ancestral informative markers. Cox proportional hazards and linear regression were performed to assess TLR polymorphism associations with HIV acquisition, peak HIV RNA levels, and infant mortality. Sex-stratified analyses of TLR7 and TLR8 were conducted due to their X-chromosome location and Bonferroni methods were used to account for multiple comparisons. For project 2, we used qualitative methods to analyze transcripts from semi-structured interviews conducted with 21 healthcare providers caring for HIV-infected children from 5 clinics in Kenya. Interview transcripts were systematically coded and conceptually analyzed using modified grounded theory and directed content analysis approaches. Resulting themes were identified related to the disclosure processes, ethical and practical rationale for different approaches, and challenges or barriers to disclosure. Results: For project 1, we found that TLR variants influenced HIV acquisition and progression. Infants with the TLR9 1635A (rs352140) variant were more likely to acquire HIV by 1 month of age (HR=1.81, 95% CI: 1.05, 3.14; p=0.033) and 12 months of age (HR=1.62, 95% CI: 1.01, 2.60; p=0.044). We also found that among 56 infants infected by 1 month of age, the TLR9 1635A allele was associated with a decrease in peak viral load (-0.58 log10 c/ml, 95% CI: -0.95, -0.22; p=0.002) whereas female infants with the TLR8 1G (rs3764880) variant had increased peak viral load (0.78 log10 c/ml, 95% CI: 0.35, 1.21; p<0.001). We also found that among female infants infected at less than 1 year of age, infants with the TLR7 rs1634319 C allele had higher peak viral load (0.80 log10 c/ml, 95% CI: 0.40, 1.20; corrected p=0.027). For project 2, we found that all health care providers interviewed believed early, supported disclosure to children is important and cited concerns for the child's health and well-being as the central rationale. Providers viewed disclosure as a longitudinal process and advocated tailoring the approach to the individual child. Providers observed that preparation, support after disclosure, and a child's personality are more relevant predictors of the impact of disclosure on the child and family than the age when diagnosis is revealed. All stressed the need to incorporate caregiver preparation and empowerment and recognized that significant barriers to disclosure included caregiver fears about child reactions, including judgment of the parent. Conclusions: We found that variations in TLRs influence HIV acquisition and progression in infants. These associations may inform novel vaccine and therapeutic strategies for pediatric HIV. Our observations among health care providers revealed a wealth of clinical approaches that can be used in guidelines to improve pediatric HIV disclosure. Better understanding the mechanisms influencing infection and how to care for HIV-infected children can help reduce the global burden of this disease.
Thesis (Ph.D.)--University of Washington, 2013
Keywords: disclosure; genetic variation; HIV; pediatric; toll-like receptor; Public health; Epidemiology; Genetics; public health genetics